1973
DOI: 10.1042/cs0450723
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamines during Sustained Isometric Exercise

Abstract: 1. Plasma catecholamine, haemodynamic and metabolic responses to sustained isometric exercise were studied in eight healthy subjects, who maintained handgrip at the 30% level of maximal voluntary contraction (MVC) for as long as possible.2. The sustained handgrip was accompanied by a significant increase in plasma noradrenaline (NA) and adrenaline (A) concentrations.3. The increase in plasma NA during handgrip was greater than that associated with heavy dynamic work involving large muscle groups.4. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 7 publications
3
25
2
1
Order By: Relevance
“…The results we obtained were similar to other studies carried out by three other authors; Kozlowski, Petro and Nutter. 14,15,10 Hence our study showed a certain rise in HR during sustained static exercise in both first and second trimesters and then return to steady state in the third trimester, whereas, the BP also showed elevated levels with sustained static exercise though at rest in the first trimester there was fall in BP and in second it was even less. Thus demonstrating a Bi-phasic hemodynamic response during pregnancy in accordance with Kuo's study.…”
Section: Discussionmentioning
confidence: 87%
“…The results we obtained were similar to other studies carried out by three other authors; Kozlowski, Petro and Nutter. 14,15,10 Hence our study showed a certain rise in HR during sustained static exercise in both first and second trimesters and then return to steady state in the third trimester, whereas, the BP also showed elevated levels with sustained static exercise though at rest in the first trimester there was fall in BP and in second it was even less. Thus demonstrating a Bi-phasic hemodynamic response during pregnancy in accordance with Kuo's study.…”
Section: Discussionmentioning
confidence: 87%
“…3). Other potential sources for this augmented Vo include an increased 02 cost of ventilatory and cardiac muscular work, metabolic stimulation arising from greatly increased catecholamine levels (Kozlowski, Brzezinska, Nazar, Kowalski & Franczyk, 1973), and also the stimulatory effect of hypocapnic alkalaemia on Vo (Cain, 1970;Karetzky & Cain, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…This response also occurred after beta-adrenergic blockade, suggesting increased alpha-adrenergic drive or responsiveness as the mechanism involved. Weidman et al (1980) have reported increased cardiovascular reactivity to infused norepinephrine in borderline hypertensive patients and postulated exaggerated peripheral vascular alpha-adrenergic receptor sensitivity as the possible mediator.Indeed, greater alphaadrenergic receptor sensitivity in certain borderline hypertensive patients could contribute to a larger pressor response to static contraction, since this type of circulatory stress is known to evoke increases in plasma norepinephrine levels (Kozlowski et al, 1973).…”
Section: Discussionmentioning
confidence: 99%